Electron-Hole Interference in an Inverted-Band Semiconductor Bilayer - Matija Karalic (American Physical Society, 2020)
Electron optics in the solid state promises new functionality in electronics through the possibility of realizing nano- and micrometer-sized interferometers, lenses, collimators, and beam splitters that manipulate electrons instead of light. Until now, however, such functionality has been demonstrated exclusively in one-dimensional devices, such as in nanotubes, and in graphene-based devices operating with p-n junctions. In this work, we describe a novel mechanism for realizing electron optics in two dimensions. By studying a two-dimensional Fabry-Perot interferometer based on a resonant cavity formed in an InAs/GaSb double quantum well using p-n junctions, we establish that electron-hole hybridization in band-inverted systems can facilitate coherent interference. With this discovery, we expand the field of electron optics in two dimensions to encompass materials that exhibit band inversion and hybridization.